Anredera Cordifolia Leaves Sub-fraction as Anti Hyperlipidemia - R. Mustarichie (Journal of Global Pharma Technology, 2020)
This study aimed to evaluate the anti-hyperlipidemic properties of the sub-fraction of the Binahong (Madeira vine, Anredera cordifolia) extract in male Wistar rats. The rats were given high-fat food every day for 3 months and pure cholesterol on weeks 0, 3, 7, and 11. Furthermore, Ethyl acetate sub-fraction of binahong leaves with 0, 12 mg/kg BW, and 0, 24 mg/kg BW doses were given orally for 3 weeks and observed for lipid profile on day 21. The result showed that sub-fractions of Madeira vine leaves decreased in triglyceride, cholesterol, and low-density lipoprotein (LDL) levels and did not influence the high-density lipoprotein level (HDL). Meanwhile, statin decreased total triglyceride, cholesterol, and the LDL level, and increased the HDL level. It concluded that Madeira vine sub-fraction with 0, 24 mg/kg BW dose presented improved results in the lipoprotein profile. Keywords: Binahong, Madeira vine, Anredera cordifolia, hyperlipidemia, ethyl acetate fraction